Activated carbon fiber felt and its preparation method and application
By preparing activated carbon fiber felts with controllable surface pore size, the problem of poor hydrogen storage performance of existing carbon nanofibers and carbon nanotubes is solved, and efficient and economical hydrogen storage and desorption effects are achieved.
Patent Information
- Application Number
- CN201910707387.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-08-01
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2039-08-01
AI Technical Summary
When existing carbon nanofibers and carbon nanotubes are used for hydrogen storage, the hydrogen storage volume is small, the desorption speed is slow, the cycle life is short, and the cost is high, making it not suitable for large-scale storage and transportation.
By using pre-oxidized fibers as raw materials, the mesh process is used to sort out the mesh tires, and the mesh is laminated and needle-punched into a felt through the lamination process. Finally, activated carbon fiber felts with controllable surface pore size are prepared through carbonization and activation treatment.
It has achieved efficient adsorption and storage of hydrogen, and has the advantages of economical, high hydrogen storage, fast desorption, long recycling life and easy to produce on a large scale.
Smart Images

Figure CN110626010B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of carbonaceous materials for hydrogen storage, and in particular to an activated carbon fiber felt and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Solid material hydrogen storage has been widely favored by researchers due to its high safety and low energy consumption. The solid hydrogen storage materials currently under research and development mainly include metal alloy materials, carbonaceous materials, inorganic porous materials, composite chemical hydrogen compound materials, and metal organic framework compound materials. Among them, the physical adsorption hydrogen storage of finger-like materials is considered to be a very promising hydrogen storage method due to its advantages of large hydrogen absorption capacity, light weight, strong anti-poisoning performance, and easy desorption. Among them, the carbonaceous adsorption materials for hydrogen storage with relatively high development potential are activated carbon fiber felt, carbon nanofibers, and carbon nanotubes.
[0004] The inventors found that although carbon nanofibers can store a large amount of hydrogen, the cost of the hydrogen storage medium is very high, and the desorption rate is slow and the cycle life is short, which is not suitable for large-scale storage and transportation. The research on carbon nanotube hydrogen storage is quite popular, but the results obtained by scholars from various countries are very different. Researchers from the National Renewable Energy Laboratory of the United States began to study carbon nanotube hydrogen storage earlier. Chambers et al. found that the hydrogen storage capacity of herringbone and plate-shaped graphite nanofibers at room temperature of 120MPa reached 67% and 53% respectively, but Gary G et al. measured the hydrogen storage performance of 9 different carbon nanotube materials at 11MPa and -80 to 500℃, and pointed out that any report on the hydrogen storage of carbon nanotube materials greater than 1% at room temperature is unreliable. In order to confirm the best hydrogen storage capacity of carbon nanotubes, Zhou Li conducted a series of experiments, and the results showed that the maximum hydrogen storage capacity of carbon nanotubes at room temperature does not exceed 0.5%, which shows that the application prospects of carbon nanotubes for hydrogen storage are not very optimistic. Summary of the invention
[0005] The inventors found in their research that activated carbon fiber felt has always been a very good carbonaceous adsorbent, and the adsorption performance of modified activated carbon fiber felt after activation will be greatly improved. In particular, the adsorption and hydrogen storage of activated carbon fiber felt materials with controllable surface pore structure characteristics has the advantages of economy, high hydrogen storage capacity, fast desorption, long cycle life and easy large-scale production. Based on this, the present invention provides an activated carbon fiber felt for hydrogen energy absorption and storage, and its preparation method and application.
[0006] The activated carbon fiber felt prepared by the present invention is a porous structure with a specific pore size on the surface, which can achieve the effect of effectively adsorbing hydrogen. The surface pore size of the single fiber of the activated carbon fiber felt of the present invention is controlled to be no higher than 0.7nm, or no higher than 0.65nm, or no higher than 0.6nm, or controlled in the range of 0.6-0.7nm. The final hydrogen absorption rate of the activated carbon fiber felt is in the range of 2.5%. The activated carbon fiber felt of the present invention can also realize the storage of adsorbed hydrogen.
[0007] Specifically, the technical solution of the present invention is as follows:
[0008] In the first aspect of the present invention, the present invention provides an activated carbon fiber felt, which is an activated carbon fiber felt, the carbon fiber felt comprising at least two layers of alternately stacked webs, and needle-punched fibers that are needle-punched through the alternately stacked webs to connect and fix adjacent stacked layers; the density of the carbon fiber felt is 0.05-0.09 g / m 3 The surface pore size of the activated carbon fiber felt is not higher than 0.7 nm, or not higher than 0.65 nm, or not higher than 0.6 nm, or is 0.6-0.7 nm.
[0009] The carbon fiber felt described in the present invention is also referred to as pre-oxidized fiber felt in the content and embodiments of the present invention, and the two can be used interchangeably in the present invention.
[0010] The mesh of the present invention is made of pre-oxidized fibers. In certain embodiments of the present invention, the pre-oxidized fibers have a tensile strength of more than 200 MPa, a tensile modulus of more than 1.0 GPa, and a fiber density of more than 1.3 g / cm 3 The carbon content of the fiber is not less than 65 wt%.
[0011] In some embodiments of the present invention, the pre-oxidized fiber is a polyacrylonitrile pre-oxidized fiber and / or a viscose-based pre-oxidized fiber.
[0012] In certain embodiments of the present invention, the single-layer mesh structure of the carbon fiber felt of the present invention has a gram weight of 10-50 g / m 2 .
[0013] In an embodiment of the present invention, the needle-punched fibers are needle-punched through the laminated web in a direction perpendicular to the laminated surface (ie, along the Z-axis direction).
[0014] In the second aspect of the present invention, the present invention provides a method for preparing the above-mentioned activated carbon fiber felt, which includes taking pre-oxidized fiber as raw material, combing it into a mesh by a combing process; the mesh is stacked by a lamination process, the stacked layers are needle-punched with needle-punched fibers to obtain carbon fiber felt, and the carbon fiber felt is carbonized and activated and then cooled to obtain activated carbon fiber felt.
[0015] The present invention firstly adopts high-performance pre-oxidized fiber as raw material, and adopts a combing process to comb it into a web; then the web is laminated by a mixed lamination process and needle-punched into a felt, and the needle-punching process controls the needle-punching density and the mixing ratio of the needle-punched fibers in the thickness direction; finally, an activation process is performed to control the flow rate and temperature of the activation medium during the activation process, so as to achieve the purpose of controlling the surface pore size of the single fiber of the activated carbon fiber felt, and an activated carbon fiber felt material with controllable surface pore structure characteristics is prepared.
[0016] The pre-oxidized fiber raw material of the present invention can be selected from polyacrylonitrile pre-oxidized fiber and / or viscose-based pre-oxidized fiber. The tensile strength of the pre-oxidized fiber is not less than 200 MPa, such as 250-300 MPa, the tensile modulus is not less than 1.0 GPa, such as 1.2-2.0 GPa, and the fiber body density is not less than 1.3 g / cm 3 , for example 1.3-1.5g / cm 3 , the carbon content of the fiber is not less than 65wt%, for example, 55-75wt%.
[0017] The web combing process of the present invention uses the high-performance pre-oxidized fiber as raw material for web combing, and the web combing ensures that the weight of the single-layer web is 10-50g / m 2 range, further to 10-45g / m 2 , for example 10g / m 2 , 40g / m 2 or 45g / m 2 When using mixed combs of different types of fibers, the mixing ratio of the combs can be flexibly adjusted according to requirements. For example, when using mixed combs of different pre-oxidized fibers, such as mixing polyacrylonitrile pre-oxidized fibers and viscose-based pre-oxidized fibers, the mixing ratio (mass ratio) can be flexibly adjusted, such as 1:1-99 or 1-99:1, such as 1:1, 1:5 or 4:1.
[0018] The web mixed layer of the present invention can be mixed with webs of different weights to adjust the density gradient of fibers in different layers. The needling of the layer is carried out in a direction perpendicular to the layer surface (i.e., along the Z axis direction), and the needling density is controlled at 10-40 needles / cm 2 Within the range, the needle-punched fiber is selected from pre-oxidized fiber, and the needle-punched fiber can be a mixture of different pre-oxidized fibers, and the mixing ratio can be flexibly adjusted. For example, the needle-punched fiber can be a mixture of polyacrylonitrile pre-oxidized fiber and viscose-based pre-oxidized fiber, and the mixing ratio (mass ratio) of the two, that is, polyacrylonitrile pre-oxidized fiber and viscose-based pre-oxidized fiber, can be 1-99:1 or 1:1-99. In the technical solution of the present invention, the ratio is 1-10:1, especially 3-8:1, which is easier to achieve the technical purpose of the present invention, such as 3:1, 4:1 or 8:1.
[0019] The carbonization activation processing technology described in the present invention adopts a process of simultaneous carbonization and activation. The pre-oxidized fiber felt (i.e., carbon fiber felt) prepared as above is sent into the furnace of an activation furnace at room temperature, and then nitrogen is introduced into the furnace. Carbonization and heating are carried out at different heating rates. After reaching a certain temperature, water vapor is introduced. After reaching a predetermined temperature, constant temperature activation is performed for a certain period of time, and finally, the felt is cooled to a certain temperature under nitrogen protection, and then naturally cooled to room temperature to complete the activation and carbonization treatment of the carbon fiber felt.
[0020] In certain embodiments of the present invention, the needle punching is performed in a direction perpendicular to the laminated surface (ie, along the Z-axis direction).
[0021] In certain embodiments of the present invention, the acupuncture density is 10-50 needles / cm 2 .
[0022] In certain embodiments of the present invention, the carbonization treatment comprises raising the temperature to 1000-1500° C. and introducing water vapor to carbonize the carbon fiber felt.
[0023] In an embodiment of the present invention, the carbonization is performed in a nitrogen atmosphere.
[0024] In certain embodiments of the present invention, the carbonization is carried out at a heating rate of 5-15°C / min to a temperature of 1000-1500°C.
[0025] In certain embodiments of the present invention, water vapor is introduced after the temperature is raised to a carbonization temperature of 1000-1500° C., and the rate of introduction of water vapor is 3-15 g / min.
[0026] In certain embodiments of the present invention, the carbonization time is 20-50 min.
[0027] In certain embodiments of the present invention, after carbonization is completed, the mixture is cooled to 150-200° C. in a nitrogen atmosphere, and then naturally cooled to room temperature.
[0028] The nitrogen described in the present invention is high-purity nitrogen with a purity of more than 99.99999% and an input pressure of not less than 0.2 MPa.
[0029] The preparation method of the present invention can control the surface pore size of the prepared activated carbon fiber felt to be no higher than 0.7nm, or no higher than 0.65nm, or no higher than 0.6nm, or within the range of 0.6-0.7nm.
[0030] The activated carbonization described in the present invention can be achieved through a carbonization activation heating device, which includes a heat preservation furnace, a heater and a temperature control device. High-purity nitrogen is introduced into the entire heat preservation furnace through a flow inlet, and the gas flow is controlled by a flow controller; at the same time, activated water vapor is introduced through the flow inlet, and the water vapor activation flow is controlled by a flow controller. Therefore, the process for preparing the activated carbon fiber felt of the present invention based on this device is particularly easy to realize industrialization. For example, an example of a carbonization activation heating device can be as follows Figure 2 The device shown.
[0031] Therefore, in the preparation method of the present invention, the carbonization activation treatment is based on the above-mentioned carbonization activation heating device, which includes: feeding the above-prepared pre-oxidized fiber felt (i.e., carbon fiber felt) into the insulation furnace 1 at room temperature, and then introducing nitrogen into the furnace through the flow inlet 4, and controlling the nitrogen introduction pressure to be not less than 0.2MPa through the flow controller 5, and controlling the heater 2 to heat up to 1000-1500°C at a heating rate of 5-15°C / min through the temperature control device 3, and then introducing activating water vapor through the flow inlet 6, and controlling the water vapor flow rate to 3-15g / min with the flow controller 7, carbonizing at a temperature of 1000-1500°C for 20-50min, and then continuing to cool to 150-200°C in a nitrogen atmosphere; and then naturally cooling to room temperature to complete the activation and carbonization treatment of the carbon fiber felt.
[0032] In the third aspect of the present invention, the present invention provides the use of the above-mentioned activated carbon fiber felt in the field of hydrogen energy storage and / or adsorption.
[0033] The surface pore size of the activated carbon fiber felt described in the present invention is not higher than 0.7nm, or not higher than 0.65nm, or not higher than 0.6nm, or 0.6-0.7nm, and its hydrogen absorption rate is within the range of 2.5%.
[0034] The activated carbon fiber felt of the present invention has the characteristic of controllable surface pore structure, and its surface pore diameter is not higher than 0.7nm, or not higher than 0.65nm, or not higher than 0.6nm, or 0.6-0.7nm. It has high adsorption activity and can be especially used for hydrogen absorption and storage. It has the advantages of economy, high hydrogen storage capacity, fast desorption, long cycle life and easy large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The drawings constituting part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. The embodiments of the present invention are described in detail below in conjunction with the drawings, wherein:
[0036] Figure 1Schematic diagram of the felt body structure of the activated carbon fiber felt of the present invention; wherein 1, 2, 3 are mesh structures, and 4 is needle-punched fiber; the felt body of the activated carbon fiber felt is obtained by laminating different meshes 1, mesh 2, and mesh 3, and then performing needle-punching treatment of different densities using needle-punched fiber 4 in the Z-axis direction.
[0037] Figure 2 The figure is a schematic diagram of a carbonization activation heating device for activated carbon fiber felt, which includes a heat-insulating furnace 1, a heater 2 and a temperature control device 3. High-purity nitrogen is introduced into the entire heat-insulating furnace 1 through a flow inlet 4, and the nitrogen flow is controlled by a flow controller 5. At the same time, water vapor for activation is introduced through a flow inlet 6, and the water vapor flow is controlled by a flow controller 7. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0039] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in the text are for demonstration purposes only.
[0040] The following embodiments can be based on Figure 2 The device shown may be implemented based on other devices having a heat preservation furnace, a heater, a temperature control device and a flow control device.
[0041] Example 1
[0042] The tensile strength is 280MPa, the tensile modulus is 1.6GPa, and the bulk density is 1.3g / cm 3 , polyacrylonitrile pre-oxidized fiber with a carbon content of 55%, the above fibers were made into a single-layer web with a weight of 40 g / m 2 The net is combed, and after combing, the net is stacked with a thickness of 10mm for Z-axis needle punching. Polyacrylonitrile pre-oxidized fiber and viscose fiber-based pre-oxidized fiber with a mixed ratio of 4:1 are selected for needle punching. The needle punching density is 10 / cm 2 The final pre-oxidized fiber felt has a bulk density of 0.05 g / m 3, place the above-mentioned fibers into an activation furnace, and introduce high-purity nitrogen with a purity of more than 99.99999% at a pressure of not less than 0.2MPa, and carry out carbonization and activation treatment simultaneously. First, the carbonization temperature is set at 1000°C, and the heating rate is 5°C / min. Then, when the carbonization temperature is reached, water vapor is introduced at a rate of 3g / min. After 20 minutes of activation treatment, the temperature is reduced to 150°C under nitrogen protection, and then naturally cooled to room temperature. The surface pore size of the finally obtained activated carbon fiber felt monofilament fiber is controlled within the range of 0.6nm, and its hydrogen absorption rate is within the range of 2.5%.
[0043] Example 2
[0044] The tensile strength is 250MPa, the tensile modulus is 1.5GPa, and the bulk density is 1.35g / cm 3 , viscose-based pre-oxidized fibers with a carbon content of 75%, and the above fibers were mixed according to a single-layer web of 10g / m 2 The net is combed, and after combing, the net is stacked with a thickness of 20 mm for Z-axis needle punching. Polyacrylonitrile pre-oxidized fiber and viscose fiber-based pre-oxidized fiber with a mixed ratio of 3:1 are selected for needle punching. The needle punching density is 10 needles / cm 2 The final pre-oxidized fiber felt has a bulk density of 0.07 g / m 3 , place the above-mentioned fibers into an activation furnace, and introduce high-purity nitrogen with a purity of more than 99.9999% at a pressure of not less than 0.3MPa, and carry out carbonization and activation treatment simultaneously. First, the carbonization temperature is set at 1500°C, and the heating rate is 15°C / min. Then, when the carbonization temperature is reached, water vapor is introduced at a rate of 15g / min. After 26 minutes of activation treatment, the temperature is reduced to 150°C under nitrogen protection, and then naturally cooled to room temperature. The surface pore size of the finally obtained activated carbon fiber felt monofilament fiber is controlled within the range of 0.6nm, and its hydrogen absorption rate is within the range of 2.5%.
[0045] Example 3
[0046] The tensile strength is 300MPa, the tensile modulus is 2.0GPa, and the bulk density is 1.5g / cm 3 , viscose-based pre-oxidized fibers with a carbon content of 60%, the above fibers were mixed according to a single-layer web tire of 40g / m 2 The net is combed, and after combing, the net is stacked with a thickness of 8mm for Z-axis needle punching. Polyacrylonitrile pre-oxidized fiber and viscose fiber-based pre-oxidized fiber with a mixed ratio of 8:1 are selected for needle punching. The needle punching density is 50 needles / cm 2 The final pre-oxidized fiber felt has a bulk density of 0.09 g / m 3, place the above-mentioned fibers into an activation furnace, and introduce high-purity nitrogen with a purity of more than 99.99999% at a pressure of not less than 0.4MPa, and carry out carbonization and activation treatment simultaneously. First, the carbonization temperature is set at 1400°C, and the heating rate is 12°C / min. Then, when the carbonization temperature is reached, water vapor is introduced at a rate of 12g / min. After 30 minutes of activation treatment, the temperature is reduced to 110°C under nitrogen protection, and then naturally cooled to room temperature. The surface pore size of the finally obtained activated carbon fiber felt monofilament fiber is controlled within the range of 0.65nm, and its hydrogen absorption rate is within the range of 2.5%.
[0047] Example 4
[0048] The tensile strength is 300MPa, the tensile modulus is 1.2GPa, and the bulk density is 1.37g / cm 3 , polyacrylonitrile pre-oxidized fiber with a carbon content of 66%, the above fibers were made into a single-layer web of 45g / m 2 The net is combed, and after combing, the net is stacked with a thickness of 15 mm for Z-axis needle punching. Polyacrylonitrile pre-oxidized fiber and viscose fiber-based pre-oxidized fiber with a mixed ratio of 4:1 are selected for needle punching. The needle punching density is 30 needles / cm 2 The final pre-oxidized fiber felt has a bulk density of 0.08 g / m 3 , place the above-mentioned fibers into an activation furnace, and introduce high-purity nitrogen with a purity of more than 99.99999% at a pressure of not less than 0.5MPa, and carry out carbonization and activation treatment simultaneously. First, the carbonization temperature is set at 1500°C, and the heating rate is 8°C / min. Then, when the carbonization temperature is reached, water vapor is introduced at a rate of 10g / min. After 33 minutes of activation treatment, the temperature is reduced to 190°C under nitrogen protection, and then naturally cooled to room temperature. The surface pore size of the finally obtained activated carbon fiber felt monofilament fiber is controlled within the range of 0.7nm, and its hydrogen absorption rate is within the range of 2.5%.
[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing activated carbon fiber felt, characterized in that: The method comprises taking pre-oxidized fiber as raw material, combing it into a web by a web combing process; laminating the web by a laminating process, needle-punching the laminated fiber to obtain carbon fiber felt, and carbonizing the carbon fiber felt and then cooling it to obtain activated carbon fiber felt; The needle punching is performed in a direction perpendicular to the laminated surface; the needle punching density is 10-40 needles / cm 2 ; The carbonization treatment includes heating to 1000-1500° C. and introducing water vapor to carbonize the carbon fiber felt; The heating rate is 5-15°C / min; the steam introduction rate is 3-15g / min; The carbonization time is 20-50min; The carbonization is carried out under a nitrogen atmosphere; After carbonization is completed, cool to 150-200°C in a nitrogen atmosphere; then cool naturally to room temperature; The carbon fiber felt comprises at least two layers of mesh, the meshes are alternately stacked, and needle-punched fibers are inserted through the alternately stacked layers of the mesh to connect and fix adjacent stacked layers; the surface pore size of the activated carbon fiber felt is not higher than 0.7nm; The mesh is made of pre-oxidized fiber; the pre-oxidized fiber has a tensile strength of not less than 200MPa, a tensile modulus of not less than 1.0GPa, and a fiber body density of not less than 1.3g / cm 3 , the carbon content of the fiber is not less than 65wt%; The pre-oxidized fibers are polyacrylonitrile pre-oxidized fibers and / or viscose-based pre-oxidized fibers; The needle-punched fibers are needle-punched through the laminated webs in a direction perpendicular to the laminated surface.
2. The method for preparing activated carbon fiber felt according to claim 1, characterized in that: The weight of single-layer mesh is 10-50g / m 2 .
3. Use of the activated carbon fiber felt according to any one of claims 1 to 2 in the field of hydrogen energy storage and / or adsorption.
Citation Information
Patent Citations
Continuous manufacturing technology for novel activated carbon fiber felt and cloth
CN103668831A
Activated carbon fiber felt
CN211416521U
Filament web type precursor fabric for activated carbon fiber fabric and method for preparing same
US20170136443A1